2021
DOI: 10.1001/jamanetworkopen.2021.37595
|View full text |Cite
|
Sign up to set email alerts
|

Family Functioning When a Child Has a Serious Illness: All for One and One for All

Abstract: A growing body of outcomes research has demonstrated that a child's serious illness can have longterm physical and mental health sequelae for both the child and his or her family. 1 These findings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, and from a systemic perspective, it is essential to look at the family as a whole and at each of its elements, as well as at the relationships they build with each other [ 10 ]. National and international studies have commented on the significant impact that a life-limiting condition has on the whole family system, contributing to changes in its relational dynamics, communication processes and structure [ 11 ]. Feudtner and colleagues [ 12 ] also concluded that, in families of children who were born substantially preterm or with critical congenital heart conditions, or who developed cancer or had progressive neurological conditions, the parents and siblings were 55% to 70% more likely to resort to healthcare and to receive diagnoses and prescriptions when compared to families with healthy children.…”
Section: Introductionmentioning
confidence: 99%
“…However, and from a systemic perspective, it is essential to look at the family as a whole and at each of its elements, as well as at the relationships they build with each other [ 10 ]. National and international studies have commented on the significant impact that a life-limiting condition has on the whole family system, contributing to changes in its relational dynamics, communication processes and structure [ 11 ]. Feudtner and colleagues [ 12 ] also concluded that, in families of children who were born substantially preterm or with critical congenital heart conditions, or who developed cancer or had progressive neurological conditions, the parents and siblings were 55% to 70% more likely to resort to healthcare and to receive diagnoses and prescriptions when compared to families with healthy children.…”
Section: Introductionmentioning
confidence: 99%
“…The literature is consensual regarding the impact of a child's potentially fatal illness on the whole family process, structure and dynamics [7,8]. Therefore, it is crucial to understand the psychological experience of the illness at all levels of the family subsystem, namely the parental caregivers, the healthy siblings and the grandparents [9].…”
Section: Introductionmentioning
confidence: 99%